Penangkapan Radikal 2,2-Difenil-1-Pikril Hidrazil oleh Ekstrak Buah Psidium guajava. L dan Averrhoa carambola L. - ABDUL ROHMAN; SUGENG RIYANTO; RIZKA DAHLIYANTI; DIMAS BAGUS PRATOMO (Fakultas Farmasi Universitas Pancasila, 2009)
Two fruits, Guava (Psidium guajava L.) and Carambola (Averrhoa cammbola L.), Which are frequently consumed by Indonesian people, have been evaluated for its activities as 2,2-diphenyl-1-picrylhidrazyl (DPPH) radical scavenging. The fruits were macerated, evaporated, dissolved in Water, partitioned with chloroform and then with aethyl acetate to afford methanolic extract and fractions of chloroform, aethyl acetate, and Water respectively. Total phenolic and total flavonoid contents of each extract and fraction Were determined by spectrophotometric technique and used to evaluate the correlation between the natural chemical contents and their activities as DPPH radical scavengers. The results showed that extracts and fractions of R guajava L. fruit have more ability to scavenge 2,2-diphenyl- 1-picrylhidrazyl (DPPH) radical than those of A. carambola L. The total phenolic and total flavonoid contents of extracts and fractions of R guajava L. fruit are also higher than those of A. cammbola L.